Analysis of video review during official judo matches: effects on referee`s decision and match results - Lima Kons, R.; Saldanha Da Silva Athayde, M.; Ceylan, B.; Franchini, E.; Detanico, D. (International Journal of Performance Analysis in Sport, 2021)
This study aimed to describe the frequency of video review (VR) used during international judo matches. The duration and time of VR occurrence and the effect of VR on subsequent referee`s decisions and match outcomes were investigated. Video recordings from the matches in which the VR was used in the 2020 Grand Slams (n = 122) were analysed. The main results showed most VR occurrences were from 1 to 2 min for female athletes (p = 0.03). Lightweight categories in both male and female groups showed the highest frequency of VR (37.3%). No significant differences were detected for VR duration and time when VR occurred considering sex and weight categories (p = 0.91, p = 0.26, respectively). A significant association was found between the type of action and the referee`s decision (p < 0.01), being score assignment the most frequent action (77.6% of male and 64.8% of female). More than 80% of the athletes (82.3% male and 78.3% female) won their matches after referees` checking. We concluded that VR is often used at the beginning of the match mainly in the female group, mostly concerning scoring attribution, which directly affected the match result in more than 80% of the cases.